Hungarológiai munkácska államtudományi hangsúlyokkal a 17. század első feléből - P. Szabó, Béla (Gerundium, 2017)
A little work of Hungarology with jurisprudential acc ents from the first half of the 17th century. Wilhelm Artner was the second person from Sopron, who became a jurist doctor in the Early Modern Age and applied his professional knowledge for the benefit of his city and Lutheran church. The present paper gives an outlook of his studies in Tubingen by introducing one of his works created there in detail. First, a draft is presented of the education and professors in the Law Faculty of Tubingen in the first third of the 17th century. Second, the circumstances of the creation and content of the disputation titled „De Regno Hungariae ejusque jure” – which was created with the co-operation of Professor Christoph Besold and Artner – is emphasized. The paper tries to eliminate the erroneous and stereotypical evaluations that have been linked with it throughout the past centuries and now the disputation is viewed as one of the first works of Hungarology.